TEH EFFECT OF MERGERS AND ACQUISITIONS TO STOCK RETURN A Comparison between Related and Unrelated Mergers and Acquisitions - , Vena Edwina Paramitha ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Changes in business increase the competition for the business players, driving the firms to expand the businesses in order to grow. This research focuses on external expansion, specifically on mergers and acquisitions. The general objective of mergers and acquisitions is to gain synergies by combining the acquiring and target firms. The objective of this research is to test on the effect of mergers and acquisitions, to acquiring firmsâ shareholders return in short (day t â 40 till day t + 5) and long term (year t â 1 and year t + 2). The samples are non-financial firms undertaking mergers and acquisitions during 2001 - 2009 and are listed in Indonesia Stock Exchange. The total sample is 25 firms. This research used daily and monthly stock prices. Short term calculates abnormal return and long term calculates Cumulative Wealth Index. The one sample test is used to see the significance of the abnormal return of a portfolio of shares in the event window. It is found that in mergers and acquisitions, there are positive significant average abnormal returns on day t â 22, t â 14 and t â 9. Mergers and acquisitions are suggested to be able to increase the value of acquiring firm shareholders in short term. For related mergers and acquisitions, there are positive significant average abnormal returns on day t â 27, t â 22, t â 14, t â 9 and t + 2. Significant positive average abnormal returns for unrelated mergers and acquisitions are experienced on day t â 38 and t â 25. It indicates that related and unrelated mergers and acquisitions increase the value of acquiring firmâs shareholders in short term. Pooled t test and comparing population means with unequal standard deviations are used to compare means cumulatively between related and unrelated mergers and acquisitions. It is found there are significant differences between the mean of related and unrelated mergers and acquisitions in short and long term. It is suggested that as a response to mergers and acquisitions, shareholders of acquiring firms experience higher returns and higher wealth in related than in unrelated mergers and acquisitions in short and long term.